The formation of endoderm-derived taste sensory organs requires a Pax9-dependent expansion of embryonic taste bud progenitor cells. - Ralf Kist; Michelle Watson; Moira Crosier; Max Robinson; Jennifer Fuchs; Julia Reichelt; Heiko Peters (PLoS Genetics)
In mammals, taste buds develop in different regions of the oral cavity. Small epithelial protrusions form fungiform papillae on the ectoderm-derived dorsum of the tongue and contain one or few taste buds, while taste buds in the soft palate develop without distinct papilla structures. In contrast, the endoderm-derived circumvallate and foliate papillae located at the back of the tongue contain a large number of taste buds. These taste buds cluster in deep epithelial trenches, which are generated by intercalating a period of epithelial growth between initial placode formation and conversion of epithelial cells into sensory cells. How epithelial trench formation is genetically regulated during development is largely unknown. Here we show that Pax9 acts upstream of Pax1 and Sox9 in the expanding taste progenitor field of the mouse circumvallate papilla. While a reduced number of taste buds develop in a growth-retarded circumvallate papilla of Pax1 mutant mice, its development arrests completely in Pax9-deficient mice. In addition, the Pax9 mutant circumvallate papilla trenches lack expression of K8 and Prox1 in the taste bud progenitor cells, and gradually differentiate into an epidermal-like epithelium. We also demonstrate that taste placodes of the soft palate develop through a Pax9-dependent induction. Unexpectedly, Pax9 is dispensable for patterning, morphogenesis and maintenance of taste buds that develop in ectoderm-derived fungiform papillae. Collectively, our data reveal an endoderm-specific developmental program for the formation of taste buds and their associated papilla structures. In this pathway, Pax9 is essential to generate a pool of taste bud progenitors and to maintain their competence towards prosensory cell fate induction.